Standardisation of minimal residual disease in multiple myeloma. (3rd July 2017) - Innao, V.; Allegra, A.; Russo, S.; Gerace, D.; Vaddinelli, D.; Alonci, A.; Allegra, A.G.; Musolino, C.
Abstract : The assessment of the effectiveness of chemotherapy in oncology cannot disregard the concept of minimal residual disease (MRD). In fact, the efforts of numerous scientific groups all over the world are currently focusing on this issue, with the sole purpose of defining sensitive, effective assessment criteria that are, above all, able to give acceptable, easily repeatable results worldwide. Regarding this issue, especially with the advent of new drugs, multiple myeloma is one of the haematologic malignancies for which a consensus has not yet been reached. In this review, we analyse various techniques that have been used to improve the sensitivity of response, aimed at reducing the cut‐off values previously allowed, as well as serological values like serum‐free light chain, or immunophenotypic tools on bone marrow or peripheral blood, like multi‐parameter flow cytometry, or molecular ones such as allele‐specific oligonucleotide (ASO)‐qPCR and next‐generation/high‐throughput sequencing technologies (NGS). Moreover, our discussion makes a brief reference to promising techniques, such as mass spectrometry for identifying Ig light chain (LC) in peripheral blood, and the assessment of gene expression profile not only in defining prognostic risk at the diagnosis but also as a tool for evaluation of response.